Investigating the Impact of Green Banking on Efficiency Strategy: Evidence from Indonesia - Putri, Rachel Noverietha; Putri, Johanna Kezia; Christanti, Rossalina; Nugroho, Albertus Henri L. (The Indonesian Journal of Accounting Research, 2024)
This study aims to investigate the application of green banking on the tendency for efficiency in banking companies. This study designs green banking using serial logic from green accounting, green innovation, and green technology in its tendency to increase company efficiency. Furthermore, stakeholders strongly influence the creation of an ethical company with three pillar objectives: social, environmental, and economic. This study explores banking companies because they are unique in their position as economic drivers but are required to be able to have an impact on society and the environment. This study uses existing banking data in Indonesia in the 2015-2021 range, which produces 231 observational data. This research found that banking companies can implement the three pillars, which include social, environmental, and economic, by encouraging stakeholders. Furthermore, in its position as an economic driver, banks will make efficiency in their budget costs so that the economic pillars are maintained without leaving the social and environmental pillars. Finally, this research has implications for the role of stakeholders who can encourage the implementation of green banking and strategies for implementing green banking for the banking industry.